The Pathological Mechanism and Potential Application of IL-38 in Autoimmune Diseases - Han, Miao-miao; Yuan, Xin-rong; Shi, Xiang; Zhu, Xing-Yu; Su, Yue; Xiong, De-Kai; Zhang, Xing-Min; Zhou, Huan; Wang, Ji-Nian (Frontiers in Pharmacology, 2021)
Interleukin-38 (IL-38), a new cytokine of interleukin-1 family (IL-1F), is expressed in the human heart, kidney, skin, etc. Recently, new evidence indicated that IL-38 is involved in the process of different autoimmune diseases. Autoimmune diseases are a cluster of diseases accompanied with tissue damage caused by autoimmune reactions, including rheumatoid arthritis (RA), psoriasis, etc. This review summarized the links between IL-38 and autoimmune diseases, as well as the latest knowledge about the function and regulatory mechanism of IL-38 in autoimmune diseases. Especially, this review focused on the differentiation of immune cells and explore future prospects, such as the application of IL-38 in new technologies. Understanding the function of IL-38 is helpful to shed light on the progress of autoimmune diseases.